Consistency of Labial Finish Line Preparation for Metal Ceramic Crowns: An Investigation of a New Bur - Kevin G. Seymour, BDS, MSc, PhD, DRD, George P. Cherukara, BDS, MClinDent, (Journal of Prosthodontics, 2008)
Previous studies have reported on the difficulties inherent in preparing the labial aspect of teeth for metal ceramic crowns with consistency and also the implications for the definitive restoration of underprepared and overangled finish lines.